2013
DOI: 10.1007/s00520-013-2040-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with the use of complementary health approaches among long-term cancer survivors

Abstract: Purpose To identify the prevalence and characteristics of long-term adult cancer survivors who use complementary health approaches (CHA). Methods Participants completed the Follow-up Care Use Among Survivors (FOCUS) Survey, a cross-sectional investigation of long-term cancer survivors. Use of CHA and reasons for use were assessed. A multivariable logistic regression model was applied to identify if predisposing, enabling and need characteristics described in the Complementary and Alternative Medicine Healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…Our criteria for CAM is identical to previous studies, which did not include the use of minerals and vitamins, for example. Our study estimates, however, are similar to those of Sohl and her colleagues (33.4%) and Fouladbakhsh and Stommel (39%) …”
Section: Discussionsupporting
confidence: 92%
“…Our criteria for CAM is identical to previous studies, which did not include the use of minerals and vitamins, for example. Our study estimates, however, are similar to those of Sohl and her colleagues (33.4%) and Fouladbakhsh and Stommel (39%) …”
Section: Discussionsupporting
confidence: 92%
“…Cancer survivors report using CAM therapies, including MBT, to help manage symptom burden [9,39]. However, prior studies have not examined MBT use by survivorship stages (e.g., one stage or across stages was examined) [33,32,31] or have included conventional approaches (religious activities and/or psychological support services) in their overall assessment of MBT use [9,32,39]. Therefore, overall MBT use among cancer survivorship stages was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined MBT use either in a single survivorship stage or cancer survivors in general (use not reported by survivorship stage). Those studies reported MBT use of 64% among survivors within 2 months post-diagnosis [31], 52% among survivors 10 to 24 months post-diagnosis [32], 27% among survivors more than 5 years post-diagnosis [33], and 22% in a general sample of cancer survivors (i.e., not examined by survivorship stage) [9]. However, these proportions may be higher than actual MBT use because religious activities (prayer) and psychosocial support services were included, which are considered more of conventional or standard of care practices rather than CAM modalities [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 High cancer-related anxiety, optimism, negative experiences with physicians, belief in the value of alternative medicine, concerns about risks associated with chemotherapy, and lack of knowledge of breast cancer treatment protocols have been reported as characteristics of patients with breast cancer who do not receive indicated chemotherapy. 68 The same set of patient characteristics also tends to be associated with high complementary and alternative medicine (CAM) use. CAM use among patients with breast cancer has been increasing over the past 2 decades 911 but few studies have evaluated how CAM use affects decisions regarding chemotherapy.…”
mentioning
confidence: 99%